Frequency and correlates of suicidal ideation and behaviors in treatment-seeking Post-9/11 Veterans. (November 2022) - Rauch, Sheila A.M.; Steimle, Lauren N.; Li, Jingyu; Black, Kathryn; Nylocks, K. Maria; Patton, Samantha C.; Wise, Anna; Watkins, Laura E.; Stojek, Monika M.; Maples-Keller, Jessica L.; Rothbaum, Barbara O.
Abstract: Objective: Post-9/11 U.S. veterans and servicemembers are at increased risk for suicide, indicating an important need to identify and mitigate suicidal ideation and behaviors in this population. Method: Using data modeling techniques, we examined correlates of suicidal ideation and behavior at intake in 261 Post-9/11 veterans and servicemembers seeking mental health treatment. Results: Our sample endorsed high rates of suicidal ideation and behavior. Approximately 40% of our sample scored in a range on the Suicide Behaviors Questionnaire-Revised (SBQ-R), indicating high clinical risk for suicide. Results from multivariate analyses indicate that greater state and/or trait depression severity, greater anger and anger expression, less impulse control, and lower rank were consistently associated with suicidal ideation and behavior across our models. Negative posttraumatic thoughts about the self, gender, and military branch of service were also significantly associated with suicidal ideation and behavior. Conclusions: Suicidal ideation and behaviors are common in veterans seeking mental health treatment. State and/or trait depression, anger and impulse control were predictors of increased risk for suicidal ideation and behavior across models. Consistencies and differences across models as well as limitations and practical implications for the findings are discussed. Highlights: Approximately 40% of veterans seeking care for PTSD reported high clinical risk for suicide. Greater depression, greater anger, less impulse control, and lower rank were associated with suicidal risk in veterans. Negative thoughts about the self, gender, and military branch were also significantly associated with suicidal risk.